Theoretical basis for ensuring technological properties of construction materials for wooden residential construction (Science journal «Technical service of agriculture, forestry and transport systems», 2025)
This study investigates the utilization of wood residues from forest fires and recycled PET to produce building materials for wooden houses. It focuses on a comprehensive technological approach involving pre-treatment and modification of damaged wood to enhance compatibility with a polymer matrix. The research optimizes composite formation with specific performance characteristics by examining burnt wood properties, component ratios, and technological parameters like temperature and pressure. It also assesses the effectiveness of microwave energy for drying and modifying wood, and for improving the water and fire resistance of the resulting composites. Furthermore, the environmental and economic viability of this waste disposal method is evaluated.This study aims to scientifically justify and develop a comprehensive approach for utilizing substantial wood residues post-forest fires for wooden house construction. This involves establishing scientific, technical, and methodological bases for producing competitive building materials with specific properties. Achieving this requires analyzing fire-damaged wood characteristics, exploring modification and composite use, and considering global trends in wooden construction alongside environmental and economic waste disposal. The research plans to develop optimal wood-polymer composite formulations using recycled PET and identify the most effective production processes, ultimately providing practical recommendations for the industrial production of eco-friendly and cost-effective building materials from secondary resources.This research scientifically validated and developed a comprehensive approach for utilizing wood residues post-fire and recycled PET for wooden house construction. Optimal pre-treatment methods minimizing thermal damage to wood's properties were identified. New data on burnt wood characteristics informed the creation of wood-polymer composite formulations with specific properties. Recycled PET proved effective as a binder, enhancing water and biological resistance. Technological recommendations for pultrusion of long profiles were developed. The study investigated flame retardants' impact on fire resistance and used microwave drying modeling to determine optimal processing parameters. Economic analysis indicated potential benefits due to reduced costs. The findings can inform industrial production of eco-friendly building materials from secondary resources.
Keywords: burnt wood; wood-polymer composites; polyethyleneterephthalate; recycling; waste materials; pultrusion; extrusion; microwave drying; rheological properties